Sarcoidosis Mimicking Chronic Sialadenitis of Parotid Gland. Issue 5 (July 2021) - Shadamarshan R, Arunkumar; Sharma, Rohit; Grewal, Ritu
Abstract : Abstract: Non-specific Chronic sialadenitis of the Parotid gland is an inflammatory disorder that leads to several anatomical and functional changes within the glandular structure. The exact etiopathogenesis of this disorder is unknown due to its relatively rare occurrence. Primary sarcoidosis of the Parotid gland masquerading the peripheral changes of Chronic sialadenitis has never been reported in literature. We report such a case of Primary Sarcoidosis of the Parotid gland presenting with non-specific chronic sialadenitis along with ipsilateral non-reducing disc displacement of the Temporomandibular joint along with its management.